Financial Feasibility Study of Waste Cooking Oil Utilization for Biodiesel Production Using ANFIS - Imam Ahmad; Irman Hermadi; Yandra Arkeman (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Consumption of fuel oil is increasing, but it is not accompanied by supply. Transportation sector is spent the most existing fuel. Therefore, it is crucial to look for alternative type of fuel such as biodiesel to overcome the fuel shortage. The purpose of this study is to investigate the feasibility on how the investment of waste cooking oil as the biodiesel material production. This study consists of two phases. First is calculating feasibility fuzzy model with the input price of biodiesel, waste cooking oil prices and interest rates, and as its output are Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C) and Payback Period (PBP). Second is predicting the feasibility of using Adaptive Neuro Fuzzy Inference System (ANFIS). The results of the analysis for each type of membership function (mf) were obtained triangular accuracy 77%, accuracy gaussian 53% and trapezoidal accuracy 61%. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7122